IDENTIFIKASI BURNOUT SHADOW TEACHER ABK PADA PEMBELAJARAN IPAS DI SDN 131/IV KOTA JAMBI - Shofy Ilaina; Hendra Budiono; Khoirunnisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the experiences of mentor teachers in dealing with fatigue and identify factors that influence the emergence of fatigue in mentors with special needs (ABK) in science learning at SD Negeri 131/IV, Jambi City. The study used a qualitative approach with a phenomenological research type. The research subjects consisted of two shadow mentor teachers of grade III and one principal as a supporting informant. Data collection was conducted through in-depth interviews and document studies. The results showed that mentor teachers experienced mental fatigue characterized by emotional exhaustion, depersonalization, and decreased personal achievement. This fatigue arises as a result of inconsistent behavior of students with special needs, difficult-to-understand science material demands, and a continuous workload. Depersonalization can be seen when teachers try to maintain distance to balance themselves, while decreased personal achievement is caused by feelings of failure when student development does not reflect expectations. This mental fatigue is influenced by various factors such as student behavior, material demands, level of engagement, work atmosphere, and support from the school. School initiatives such as monthly meetings, providing breaks, and personal communication also help reduce the burden felt by mentor teachers.